Բոգդան Ասլանովի ուղեգրությունը - Չոբանյան, Պավել («Զանգակ - 97»)
The article deals with the description of Bogdan (Baghdasar) Aslanov's (captain of Russian military scrvice) travel to Persia and Afghanistan in 1764-1765. After his return he presented a report named "Secrct Note" to Russian authorities. In the description we find a lot of interesting information about the political and economical Situation in that countries as well as about the diplomatic and military-political relations between China and Afghanistan in the mid of XVIII century.
Keywords: Պատմություն